Gender, concept and uses - Aissaoua, Wahiba (Social Sciences Journal, 2020)
The concept of gender from a cognitive perspective is used in various fields (literature, law, economics, media, politics ...) and according to multiple approaches: psychology, anthropology, sociology and others. This argument allows for broadening the perspectives of science in order to better understand the characteristics Social environment and acceptable interpretation of the forms of interaction and communication within the community, and to become the most important analytical statements in the field of development. This paper seeks to provide a comprehensive definition of the concept of gender, in order to remove the ambiguity and confusion that surrounds him, focusing on its Components and basic concepts, relationships and uses that constitute the theoretical frameworks for gender, explaining how to handle and use this concept.